Kruppel-like factor 4 (KLF-4) inhibits the epithelial-to-mesenchymal transition and proliferation of human endometrial carcinoma cells. (1st September 2016) - Wang, Xiaoli; Li, Xiaoyan; Huang, Cuiping; Li, Lei; Qu, Hongmei; Yu, Xiaoyan; Ni, Huijie; Cui, Qing
Abstract: Kruppel-like factors (KLFs) are a group of transcriptional regulators, being tumor-suppressive in various types of cancers, but not clear in human endometrial carcinoma (EC). We investigated the KLF-4 expression in both mRNA and protein levels in 29 EC specimens with RT-qPCR and Western blotting methods, and then to determine its promotion to Epithelial-to-mesenchymal transition (EMT) and proliferation of EC Ishikawa cells, via analyzing EMT-associated markers and via CCK-8 and colony forming assay. We found the downregulation of KLF-4 in the 29 EC specimens, correlating with the EC malignance. Moreover, we confirmed reduced levels of EMT and cell proliferation of Ishikawa cells post-KLF-4 overexpression. In conclusion, the significantly reduced KLF-4 correlated with the EC malignance. And the overexpressed KLF-4 promoted the EMT and proliferation of EC cells in vitro . The present study recognized the tumor suppressive role of KLF-4 in EC.